Dakwah di Tengah Isi Radikalisme - Muhlis; Muliaty Amin (RETORIKA : Jurnal Kajian Komunikasi dan Penyiaran Islam, 2020)
Radicalism has become an issue that is never absent to discuss. Moreover, current developments, such as the issue of radicalism, also continue to develop. Radicalism is something that needs to be watched out for because its existence is quiet like an underground movement which is quite difficult to detect. However, evidence of the existence of radicalism in Indonesia still exists even today. The da'wah movement which is an effort to prevent and overcome radicalism movements must develop in accordance with the current developments. Da'wah must be packaged more attractively and involve all parties in the current problem of radicalism. Da'wah with a structural and cultural approach can be a strategy in preventing and overcoming radicalism.